Backlash by men against the socio-economic and political promotion of women in Europe - Parth, Anne-Marie (Social Sciences, 2022)
The gender gap in voting for far-right parties is significant in many European countries. While most studies focus on how men and women differ in their nationalist and populist attitudes, it is unknown how the socio-economic and political promotion of women is associated with the gender gap in far-right political orientation. The following paper compares the effect of four different spheres of gender equality on this gender gap. By estimating multilevel logit models for more than 25 European countries and testing the mechanism via a socially conservative attitude toward gendered division of work, I find that the visible field of representation in particular—measured by the share of women in parliament and women on boards—is associated with a gender gap in far-right orientation. This paper contributes to the literature in two important ways: first, it combines policy feedback with cultural backlash theory, enlarging the scope of both theories; second, it demonstrates the importance of gender equality policies for the study of the far-right gender gap.
Gesehen am 01.08.2023